Dr. Hamid Abdullah Jalab Altulea, Senior Lecturer, Department of Computer System & Technology, Faculty of Computer Science & Information Technology, University of Malaya, 50603 Kuala Lumpur, MALAYSIA - Jalab, Hamid Abdullah (University of Malaya, 2018)
Researcher Profile Poster by Frontier Science Research Cluster (FSRC), University of Malaya.